Outpatient Satisfaction with Health Insurance Drug Dispensing Quality at the Pharmacy of Ho Chi Minh City University of Medicine and Pharmacy Hospital - Thi Hai Yen, Nguyen; Van Dat, Truong; Ngoc Ha, Thai; Hue Ngan, Thai; Dang Tu Nguyen, Le; Pham Luyen, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3DO - 10.25073/2588-1132/vnumps.4223, 2020)
This paper conducts a descriptive cross-sectional study to determine the outpatient satisfaction with health insurance drug dispensing at the pharmacy of Ho Chi Minh City University of Medicine and Pharmacy Hospital in 2019 through a survey questionnaire. The study results show that the outpatient satisfaction was influenced by 4 factors: reliability, assurance, empathy and tangibility, among which, reliability was the most influential one (42%). Generally, the outpatient satisfaction with the health insurance drug dispensing ranged from “Satisfied” to “Absolutely satisfied” (4.19 – 4.36). The study also shows a low level of satisfaction with drug dispensing time and some other aspects of the drug dispensing, which suggests that suitable measures should be taken by the hospital to improve its outpatient drug dispensing service. Keywords Satisfaction, service quality, drug dispensing, Ho Chi Minh City University of Medicine and Pharmacy Hospital. References [1] E. Zarei, A. Daneshkohan, B. Pouragha et al, An empirical study of the impact of service quality on patient satisfaction in private hospitals Iran, Global journal of health science, 7(1) (2014) 1-9. https://doi.org/10.5539/gjhs.v7n1p1 [2] R. Thornton, N. Nurse, L. Snavely et al, Influences on patient satisfaction in healthcare centers: a semi-quantitative study over 5 years, BMC Health Services Research, 17 (2017). https://doi.org/10.1186/s12913-017-2307-z [3] Le Ba Tiep, Surveying the satisfaction of outpatient with health insurance procedures at the clinic – Nguyen Trai Hospital, Ho Chi Minh City. Specialized Pharmacist of 1st grade, 2017 (in Vietnamese) [4] Phung Duc Nhat, Phan Thi Hieu, Tran Ngoc Phuong, Dien Ngoc Trang, Nguyen Thi Tuyet Van, Customer satisfaction with health care services at the center of injury prevention and non-communicable diseases, Medical Journal Ho Chi Minh City, 18(6) (2013) 646-652 (in Vietnamese) [5] A. Parasuraman, V.A.Zeithaml, L.L.Berry, Servqual: A multiple – item scale for measuring consumer perception of service quality, Journal of Retailing, 64 (1988) 12-40. [6] Nguyen Tran Huy Duc, Measuring the satisfaction of outpatient patients with the quality of service at Ho Chi Minh City Public Hospital, Master thesis, 2013 (in Vietnammese). [7] Phan Thi Thuy Duong, Factors affecting the satisfaction of customer with treatment services covered by health insurance in Gia Lai province, Master thesis, 2016 (in Vietnamese). [8] Nhu Ngoc Thanh, The impact of service quality on patient satisfaction at Hai Duong Children of Hospital, Master thesis, 2013 (in Vietnamese). [9] Hoang Trong, Chu Nguyen Mong Ngoc, Analyze research data with SPSS volumes 1 and 2, Hong Duc Publishing House, Ho Chi Minh City, 2008 27-46 (in Vietnamese). [10] J.D. Evans, Straightforward Statistics for the Behavioral Sciences, Brooks/Cole Publishing Company, Pacific Grove, 1996. [11] Ministry of Health, Vietnam Policy on Satisfaction Index 2018, 44 (in Vietnamese). [12] Huynh Bao Tuan, Pham Le Khanh Linh, Tran Minh Nhut, Lean application for the pharmacy in medication administration to out-patients with health insurance at Hoan My Saigon Hospital, Science & Technology Development Journal, 20 (4) (2017) 34-40 (in Vietnamese). [13] H. Koning, J. Verver, J. Heuvel et al, Lean Six Sigma in Healthcare, Journal for healthcare quality :official publication of the National Association for Healthcare Quality, 28 (2006) 4-11. https://doi.org/10.1111/j.1945-1474.2006.tb00596.x [14] J. Heuvel, R. Does, H. Koning, Lean Six Sigma in a hospital, Int. J. Six Sigma and Competitive Advantage, 2 (2006) 377-388. https://doi.org/10.1504/IJSSCA.2006.011566.